Neurocardiac Axis Physiology and Clinical Applications - Caroline Plott; Tarek Harb; Marios Arvanitis; Gary Gerstenblith; Roger Blumenthal; Thorsten Leucker (International Journal of Cardiology: Heart & Vasculature, 2024)
The neurocardiac axis constitutes the neuronal circuits between the arteries, heart, brain, and immune organs (including thymus, spleen, lymph nodes, and mucosal associated lymphoid tissue) that together form the cardiovascular brain circuit. This network allows the individual to maintain homeostasis in a variety of environmental situations. However, in dysfunctional states, such as exposure to environments with chronic stressors and sympathetic activation, this axis can also contribute to the development of atherosclerotic vascular disease as well as other cardiovascular pathologies and it is increasingly being recognized as an integral part of the pathogenesis of cardiovascular disease. This review article focuses on 1) the normal functioning of the neurocardiac axis; 2) pathophysiology of the neurocardiac axis; 3) clinical implications of this axis in hypertension, atherosclerotic disease, and heart failure with an update on treatments under investigation; and 4) quantification methods in research and clinical practice to measure components of the axis and future research areas.